VPH-6 Semi Quantitative Analysis of Rabies Entrance into Pisang Island from Pesisir Barat District of Lampung - Tri Guntoro; . Putri; . Ferro (Hemera Zoa, 2018)
Rabies is a zoonotic infectious animal disease. Genesis of rabies is feared among people because it almost ends in death. The disease is caused by the virusrabies, the genus Lyssavirus of the family Rhabdoviridae (Muleyaetal., 2012). The case of rabies / lyssa has long been recognized by the public and has been widespread in several countries of the world. Human deaths from rabies in Africa and Asia are estimated at 55,000 people per year (Knobel et al., 2005). The presence of rabies in Indonesia was first reported in the iPhones of West Java in 1884. To date, rabies in Indonesia still poses a major problem from the public health aspect with an average reported death rate of 125 people per year (Sedyaningsih, 2011). Therefore, rabies is grouped into strategic diseases and is given priority in its prevention, control and eradication.Pisang Island is located inPesisir Barat District which is one of the foreign tourist destinations. It is located very close to the west coastal district which has a high bite case (attached). It is therefore necessary to analyze the risk of rabies entry from the Pesisir Barat district to Pisang Island.